HOW PROVABLY GRACEFUL ARE THE TREES? - Slater, Peter J. (IndoMS, 2011)
Given the inability to prove that all trees are graceful, can we at least say something positive about their gracefulness? Two problems of this type are presented.DOI :Â http://dx.doi.org/10.22342/jims.0.0.25.133-136